The second Covid-19 wave of 2020 in Italy: a brief analysis - Fabiano, Nicola; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: Based on the results obtained previously, the second wave of Covid-19 infection is analyzed and some predictions on its evolution are given.Methods: A model of population growth giving a differential equation has been used to describe the pandemic wave.Results: The second wave of infection is essentially on its peak in the middle of November 2020 and will not decrease very soon.Conclusions: The second wave is not going to end in the year 2020 and it will take some time before a status of relative normality is restored.
Keywords: Coronavirus; COVID-19; differential equation; data fit